1991
DOI: 10.1111/j.1346-8138.1991.tb03129.x
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive Steatocystoma Multiplex on the Scalp

Abstract: We report a 71-year-old Japanese woman who noticed approximately 120 small yellowish cysts on the scalp from nine months before her first visit. An incision made into the cysts discharged oily yellow material. Biopsy of a lesion disclosed that the cysts had typical features of steatocystoma multiplex histologically. This case was a unique eruptive variety of steatocystoma multiplex on the scalp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Some authors have reported that steatocystoma multiplex has been associated with ichthyosis and koilonychia, pachyonychia congenita, acrokeratosis verruciformis of Hopf, hypertrophic lichen planus, hypohidrosis, hypothyroidism, hidradenitis suppurativa and hypotrichosis 4,18,19 . For steatocystoma multiplex limited to the scalp, there have been no reports about specific causative factors and the relationship with other disorder, as was the case for our patient 3,4,[7][8][9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have reported that steatocystoma multiplex has been associated with ichthyosis and koilonychia, pachyonychia congenita, acrokeratosis verruciformis of Hopf, hypertrophic lichen planus, hypohidrosis, hypothyroidism, hidradenitis suppurativa and hypotrichosis 4,18,19 . For steatocystoma multiplex limited to the scalp, there have been no reports about specific causative factors and the relationship with other disorder, as was the case for our patient 3,4,[7][8][9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…It is a distinct clinical condition that's characterized by numerous small, skincolored or yellowish, cutaneous cysts 2 . The lesions typically appear in childhood or early adulthood, but in some patients the lesions have developed late in life 3,4 . The cysts are located principally on the axillae, groin, trunk, scrotum and proximal extremities and they are rarely localized to the face and scalp [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But some cases of steatocystoma multiplex seen on face and scalp can arise sporadically without any family history, as was the case seen in our patient [4]. It usually begins in late childhood and persists indefinitely, but in some patients the lesions have developed late in life [5]. Steatocystoma multiplex localized in the face and scalp has been divided into the following three types:…”
Section: Case Reportmentioning
confidence: 99%
“…(i) Facial papular variant type (ii) Sebocystomatosis and (iii) Cysts located exclusively on scalp [5]. The etiological factors of steatocystoma multiplex are still unclear but trauma infection and immunological events have been proposed as some reasons [6].…”
Section: Case Reportmentioning
confidence: 99%